Fistules obstétricales dans la province du Haut-Katanga, République Démocratique du Congo: à propos de 242 cas - Nsambi, Joseph Bulanda (Pan Afr Med J, 2018)
Obstetric fistulas are a major public health problem in poor countries. This study aimed to describe the epidemiological, clinical and therapeutic features of obstetric fistulas in northern Katanga province, Democratic Republic of the Congo. We conducted a descriptive cross-sectional study of 242 patients with obstetric fistula living in northern Katanga province from September 2009 to December 2013. The parameters studied included maternal sociodemographic data, obstetric and neonatal parameters, specific features of the fistula as well as management approach and outcome. Variables were analyzed using Epi Info 7.1 software. Out of 242 patients with obstetric fistula, 229 (95%) patients delivered vaginally and among them 74.6% delivered at home. In 93,4% of cases the new-born died in the perinatal period. The average age of patients was 27.9 ± 10.3 years. One out of six patients had less than 20 years and in general almost 1 out of 2 patients had less than 25 years. Seven out of ten patients had a parity of less than 3 and the average parity was 2.5±2.0. Ninety percent of patients had a low educational level and 95% lived alone. The patients had, on average, a history of fistula of more than 4.7±4.4 years, it was a vesico-vaginal fistula (96%) type 2-3 (37%) and it was repaired using a transvaginal approach (67%). The average failure rate was 14%. Obstetric fistula is a real public health problem in our environment and it deserves further consideration to be eradicated.